Stratigraphy of a Lateglacial lake basin sediment sequence at Turret Bank, upper Glen Roy, Lochaber: implications for the age of the Turret Fan. Issue 1 (February 2017) - Lowe, J.J.; Palmer, A.P.; Carter-Champion, A.; MacLeod, A.; Ramírez-Rojas, I.; Timms, R.G.O.
Abstract: New lithostratigraphical, pollen-stratigraphical and tephrostratigraphical data are presented for a sediment sequence at Turret Bank, a site that lies close to the confluence of the River Turret with the River Roy in Lochaber, the western Scottish Highlands. The site is also adjacent to the inner margin of a major gravel fan, the Glen Turret Fan, the age of which has been debated and has a crucial bearing on the overall sequence of events in Glen Roy, especially concerning the maximum limit of Loch Lomond Readvance (Younger Dryas) ice. Several lines of evidence point to the sediment sequence at Turret Bank having been wholly deposited during the Loch Lomond Stadial-early Holocene transition: (i) the pollen sequence is typical for this transitional period; (ii) varved deposits preserved in the sequence bear a strong resemblance to mid-Stadial varves in a regional master varve scheme for Glen Roy and vicinity (the Lochaber Master Varve Chronology); and (iii) an early Holocene tephra – the Askja-S Tephra – is preserved within the sequence. Some limitations with the new data are considered, but it is concluded that the coherent integration of lithostratigraphic, geomorphological, pollen-stratigraphical and tephrostratigraphical data point to the likelihood that Loch Lomond Readvance ice extended to the inner margin of the Glen Turret Fan, and that the fan was probably constructed by glacial meltwaters at this time.